Penyelesaian Kasus Khalwat melalui Peradilan Adat Aceh - Muntazar Muntazar; A. Hamid Sarong; Mohd. Din (Sharia and Law Faculty, 2017)
Aceh Qanun No. 6 of 2014 on the Law Jinayat Article 24 Qanun said,